2016
DOI: 10.2341/13-259-l
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stain Penetration by Beverages in Demineralized Enamel Treated With Resin Infiltration

Abstract: Both Icon and control surfaces exhibit stain penetration by different beverages (iced tea, grape juice, and coffee). However, resin-infiltrated enamel surfaces allow significantly less depth of stain penetration compared to untreated surfaces. The iced tea group presents greatest depth of stain penetration, followed by grape juice, methylene blue, and coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The study showed a much lower tendency of infiltrated enamel for discolouration compared to demineralised enamel, which remains in contradiction with the results obtained by Leland et al [43]. Interesting information is also provided by the results of the study by Lee et al, carried out on human teeth, but with the use of other research methods [22]. Under a light microscope the penetration depth of external dyes in heat-treated and demineralised enamel not subjected to infiltration was assessed.…”
Section: Analysis Of Literaturementioning
confidence: 61%
See 4 more Smart Citations
“…The study showed a much lower tendency of infiltrated enamel for discolouration compared to demineralised enamel, which remains in contradiction with the results obtained by Leland et al [43]. Interesting information is also provided by the results of the study by Lee et al, carried out on human teeth, but with the use of other research methods [22]. Under a light microscope the penetration depth of external dyes in heat-treated and demineralised enamel not subjected to infiltration was assessed.…”
Section: Analysis Of Literaturementioning
confidence: 61%
“…Under a light microscope the penetration depth of external dyes in heat-treated and demineralised enamel not subjected to infiltration was assessed. In demineralised enamel, dyes penetrated deeper than enamel subjected to infiltration, and this was a statistically significant difference [22]. Therefore, in accordance with the assumptions of the infiltration technique, the resin blocks or limits diffusion paths for dissolved minerals and microorganisms, but also for potential colourants.…”
Section: Analysis Of Literaturementioning
confidence: 81%
See 3 more Smart Citations